2010
DOI: 10.1084/jem.20100844
|View full text |Cite
|
Sign up to set email alerts
|

Transient activation of c-MYC expression is critical for efficient platelet generation from human induced pluripotent stem cells

Abstract: A specific kinetic pattern of c-MYC expression is essential for optimal generation of functional platelets from human induced pluripotent stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
257
0
4

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 307 publications
(281 citation statements)
references
References 45 publications
11
257
0
4
Order By: Relevance
“…To examine whether iMKderived platelets are functional, ex vivo thrombus formation under flow condition was also tested, and functionality was confirmed [3]. As demonstrated in previous papers [8,10], it should be proved in the future that iMK-derived platelets circulate in NOG mice and are able to form thrombus in vivo.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…To examine whether iMKderived platelets are functional, ex vivo thrombus formation under flow condition was also tested, and functionality was confirmed [3]. As demonstrated in previous papers [8,10], it should be proved in the future that iMK-derived platelets circulate in NOG mice and are able to form thrombus in vivo.…”
mentioning
confidence: 78%
“…On the other hand, iPSC-or ESCmediated generation of platelets in humans has been demonstrated by Eto and colleagues [7,8]. They revealed that a transient activation of c-Myc during megakaryopoiesis is critical for efficient platelet production from human iPSCs [8] (Figure 1); that is, reactivation of c-Myc after reprogramming should be followed by reduction of c-Myc expression for further maturation.…”
mentioning
confidence: 98%
See 3 more Smart Citations